Transformasi Sosial Emosional AUD melalui Lingkungan Belajar - Helia Nurmala, Nuke; Wahyudin, Erik (Mulya Literasi Publishing, 2025)
This research study is based on the obstacles observed at Al Misbah Cibulan Cidahu Kindergarten in the management of emotions and peer interaction. One of the reasons is an inappropriate strategy and inadequate facilities. With a qualitative approach and case study design, data is collected through structured interviews, observations, and document reviews involving principals, teachers, students, and parents. The findings of the study include three main focuses, namely (1) the characteristics of the learning environment that support social-emotional development; (2) internal and external factors that support or inhibit this transformation; and (3) strategies that educators can use to create a conducive, empathetic, and inclusive learning environment. These findings offer practical insights for educators and policymakers on improving the quality of early childhood education, particularly in terms of the physical, social, and psychological aspects of designing learning environments for young children